Factors affecting the probability of recurrence of the Cushing’s disease within 3 years after effective neurosurgical treatment - Elena Y. Nadezhdina; Olga Y. Rebrova; Oksana V. Ivashenko; Vilen N. Azizyan; Svetlana D. Arapova; Andrey Y. Grigoriev (Эндокринная хирургия, 2018)
Background. Cushings disease (СD) is а severe neuroendocrine disease that can rapidly progress with the development of severe complications of hypercorticism requiring immediate treatment. The main method of treatment is a neurosurgical operation, the effectiveness of which at the present time can reach 80% or more, however, about a quarter of patients after successful neurosurgical treatment experience reccurence.